2003
DOI: 10.1128/jb.185.13.3726-3734.2003
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Catalytic Activity of a Cell Division-Specific Transpeptidase In Vivo with β-Lactams

Abstract: Penicillin-binding protein 3 (PBP3; also called FtsI) is a transpeptidase that catalyzes cross-linking of the peptidoglycan cell wall in the division septum of Escherichia coli. To determine whether the catalytic activity of PBP3 is activated during division, we assayed acylation of PBP3 with three ␤-lactams (cephalexin, aztreonam, and piperacillin) in growing cells. Acylation of PBP3 with cephalexin, but not aztreonam or piperacillin, appeared to be stimulated by cell division. Specifically, cephalexin acylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 44 publications
3
62
0
Order By: Relevance
“…Recently, it has been reported that E. coli PBP3 (FtsI) becomes acylated at a faster rate in dividing cells than in nondividing cells, and the authors suggested that the enzyme's TP activity may become activated during septation (29). Based on those observations and our results reported here, we propose a model where PBPs could exist in nondividing cells in inactive (''closed'') states.…”
Section: Discussionmentioning
confidence: 48%
“…Recently, it has been reported that E. coli PBP3 (FtsI) becomes acylated at a faster rate in dividing cells than in nondividing cells, and the authors suggested that the enzyme's TP activity may become activated during septation (29). Based on those observations and our results reported here, we propose a model where PBPs could exist in nondividing cells in inactive (''closed'') states.…”
Section: Discussionmentioning
confidence: 48%
“…Although FtsI inhibitors are often used to induce E. coli to filament (11), scattered reports indicate that they can also induce rapid cell lysis (12,13). We found that midcell lysis is reproducible and requires cells to be growing exponentially in rich media at low cell densities [Ͻ10 8 cells/ml, supporting information (SI) Fig.…”
Section: Cephalexin Induces Filamentation Followed By Lysis At Low Cellmentioning
confidence: 80%
“…To further investigate whether cell wall synthesis limits the progression of septum closure, we analyzed septum closure rates in a temperature-sensitive mutant strain, MCI23, in which the total cellular activity of the essential cell wall transpeptidase, FtsI (also known as PBP3), is reduced even at permissive temperatures, likely because of decreased thermostability of the protein (101). FtsI localizes to the septum at the onset of constriction (102,103) and exhibits stimulated transpeptidase activity in dividing cells compared with nondividing cells (104). If FtsI's PG synthesis activity, rather than Z-ring contraction, were a primary driver of septum closure, we would expect the lowered FtsI activity in the MCI23 strain to result in a reduced rate of septum closure.…”
Section: Decreased Activity Of Pg Synthesis Enzyme Ftsi Decreases Septummentioning
confidence: 99%